2022
DOI: 10.1038/s41598-022-13295-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of cry3Bb1 and cry3 genes for enhanced resistance against insect pests in cotton

Abstract: Transgenic technology played a crucial role in developing insect-resistant plants resulting in the reduced application of pesticides. This article reports the expression of two cry proteins (Cry3Bb1 and Cry3) in cotton for enhanced resistance against chewing insect pests. The aforementioned genes were synthetically developed and were cloned under appropriate regulatory sequences followed by transformation into Eagle-2 genotype (Gossypium hirsutum) of cotton through shoot apex-cut Agro-infiltration. The transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Upland cotton is one of the most important agro-industrial crops all around the world (Zafar et al 2022). It's not only the leading ber source but also the third-largest eld crop in terms of edible oilseed (Ma et al 2016).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Upland cotton is one of the most important agro-industrial crops all around the world (Zafar et al 2022). It's not only the leading ber source but also the third-largest eld crop in terms of edible oilseed (Ma et al 2016).…”
Section: )mentioning
confidence: 99%
“…It was reported that half of the yield losses were caused by pest feeding directly and pathogenic infection indirectly (McCook and Vandermeer 2015). Transgenic cotton expressing a toxic protein derived from Bacillus thuringiensis (Bt) effectively suppressed several agricultural pests such as Coleoptera, Lepidoptera, and Diptera without harming human health and the environment (Park et al 2009;Zhao et al 2016;Zafar et al 2022). With the worldwide cultivation of transgenic cotton, Helicoverpa armigera (Hübner), Pectinophora gossypiella, and some lepidopteran insects are controlled effectively, but no obvious inhibition on other insects (Helen 2006;Tabashnik 2010).…”
Section: )mentioning
confidence: 99%
“…The negative environmental factors including drought, heat and cold stresses greatly affect the overall production of cotton Zafar et al 2021). The negative environmental factors including cold, salt, drought, heat, fungi, viruses, bacteria, nematodes and insects adversely affect plants' growth, development, productivity and quality (Mammadov et al 2018;Zafar et al 2022a;Zafar et al 2020;Zhu et al 2013). Advanced molecular techniques have been successfully implemented to reveal and understand the mechanism of plant responses and their adaptability to environmental challenges (Zhu 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A decrease of 17.5% in cotton production was observed during last year due to biotic and abiotic factors. Cotton ginning was also declined by 12.74% due to decline in production Zafar et al 2022a;Zafar et al 2022b). Pakistan's cotton yield has been reduced in the last few years due to many reasons.…”
Section: Introductionmentioning
confidence: 99%